2017
DOI: 10.1371/journal.pone.0170665
|View full text |Cite
|
Sign up to set email alerts
|

25-hydroxyvitamin D3 and 1,25-dihydroxyvitamin D3 exert distinct effects on human skeletal muscle function and gene expression

Abstract: Age-associated decline in muscle function represents a significant public health burden. Vitamin D-deficiency is also prevalent in aging subjects, and has been linked to loss of muscle mass and strength (sarcopenia), but the precise role of specific vitamin D metabolites in determining muscle phenotype and function is still unclear. To address this we quantified serum concentrations of multiple vitamin D metabolites, and assessed the impact of these metabolites on body composition/muscle function parameters, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 32 publications
(41 reference statements)
4
60
1
Order By: Relevance
“…(34) In vitro studies further support this notion, showing alterations in calcium signaling pathways and myocellular gene expression after 25 (OH)D or 1,25(OH) 2 D exposure. (35)(36)(37) However, in agreement with the current study, improvements in serum 25(OH)D have also shown a neutral effect on muscle-related outcomes, including a lack of an effect on muscle strength, (38,39) muscle function, or the risk of falling. (40,41) Although alleviating vitamin D deficiency (<20 nmol/L) through supplementation improves muscle-related outcomes, (32)(33)(34)38,42,43) whether such effects occur in the absence of deficiency in both adolescents and adults (>20 nmol/L) is still unclear.…”
Section: Discussionsupporting
confidence: 90%
“…(34) In vitro studies further support this notion, showing alterations in calcium signaling pathways and myocellular gene expression after 25 (OH)D or 1,25(OH) 2 D exposure. (35)(36)(37) However, in agreement with the current study, improvements in serum 25(OH)D have also shown a neutral effect on muscle-related outcomes, including a lack of an effect on muscle strength, (38,39) muscle function, or the risk of falling. (40,41) Although alleviating vitamin D deficiency (<20 nmol/L) through supplementation improves muscle-related outcomes, (32)(33)(34)38,42,43) whether such effects occur in the absence of deficiency in both adolescents and adults (>20 nmol/L) is still unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, correlation analysis in the current study did not show a robust correlation between HGS and either serum 25(OH)VitD or 25(OH)VitD 3 levels. It was previously reported that 1α,25(OH) 2 VitD 3 , not the inactive form 25(OH) 2 VitD 3 , is positively correlated with limb strength in non‐CKD individuals . Also, the 25(OH)VitD 3 level can not directly reflect the 1α,25(OH) 2 VitD 3 level due to their different synthase and synthetic positions .…”
Section: Discussionmentioning
confidence: 96%
“…It was previously reported that 1α,25(OH) 2 VitD 3 , not the inactive form 25(OH) 2 VitD 3 , is positively correlated with limb strength in non-CKD individuals. 25 Also, the 25(OH)VitD 3 level can not directly reflect the 1α,25(OH) 2 VitD 3 level due to their different synthase and synthetic positions. 26 A direct study on serum 1α,25 (OH) 2 VitD 3 level and muscle strength was needed to confirm this relationship.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, some studies, using specific and sensitive immunohistochemical assays, showed that the vitamin D receptor was undetectable in skeletal, cardiac and smooth muscle, suggesting an indirect involvement of the hormone on the muscles themselves [18]. On the other hands, subsequent studies revealed that VDR can be localized in the nucleus of human muscle cell lines, myoblasts [19] and adult skeletal muscle [20,21].…”
Section: Role Of Vitamin D On the Skeletal Muscle Systemmentioning
confidence: 99%